2015
DOI: 10.1038/nphys3530
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-induced superconductivity in electrochemically etched ultrathin FeSe films on SrTiO3 and MgO

Abstract: (1 − / (0)) with ϕ 0 and ξ(0) being the flux quantum and the GL coherent length at zero temperature, respectively, we obtained ξ(0) = 2.0 nm, which is around two times shorter than the bulk value 3 .8 Getting back to the thickness dependence of T c on in Figs. 2c and 2d, we note that the first single step superconducting transition appears at the thickness of 9.6 nm and 5.9 nm for sample A and N, respectively. The appearance of high-T C superconductivity in the rather thicker conditions offers us to consider t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
213
4
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(236 citation statements)
references
References 34 publications
14
213
4
5
Order By: Relevance
“…The origin of this phenomenon is under debate with both interfacial doping and substrate-modified electron-phonon coupling implicated in the enhancement 80 . The transition temperature of few-layer FeSe can also be modified through electrostatic tuning 81,82 (Fig. 3b).…”
Section: Creating Macroscopic Quantum Coherencementioning
confidence: 99%
“…The origin of this phenomenon is under debate with both interfacial doping and substrate-modified electron-phonon coupling implicated in the enhancement 80 . The transition temperature of few-layer FeSe can also be modified through electrostatic tuning 81,82 (Fig. 3b).…”
Section: Creating Macroscopic Quantum Coherencementioning
confidence: 99%
“…Moreover, even if, here, the proposed process is not electrochemical, it was shown recently that etching with an IL can proceed in a controlled way. 33 Further experiments should be performed to elucidate these points, but from atomic force microscopy (AFM) performed after EDL gating, we can already say that no topographical damage could be seen down to AFM in-plane resolution (%10 nm).…”
mentioning
confidence: 99%
“…Shiogai et al [153], Lei et al [154] and Hanzawa et al [155] independently demonstrated enhancement of T onset c to above 40 K by electron doping using an electric double-layer transistor (EDLT) technique. As the gate voltage is changed, a rapid increase of T c and sign reversal of Hall coefficient are simultaneously observed, suggesting that enhancement of T c is related to the Lifshitz transition (disappearance of hole Fermi surface) [154].…”
Section: -System MLmentioning
confidence: 99%
“…As the gate voltage is changed, a rapid increase of T c and sign reversal of Hall coefficient are simultaneously observed, suggesting that enhancement of T c is related to the Lifshitz transition (disappearance of hole Fermi surface) [154]. Shiogai et al successfully controlled thickness of the grown FeSe films by electrochemical etching using EDLT, and investigated the dependence of T c on thickness and substrate [153,156]. They found that electron-doped FeSe films on both STO and MgO substrates show almost the same T c of approximately 40 K. These results seem to be inconsistent with the results of the in situ measurements, which may be due to differences in condition of pretreatment for substrates and post-annealing.…”
Section: -System MLmentioning
confidence: 99%